EFFECT OF FERTILISER AND IRRIGATION ON FORAGE YIELD AND IRRIGATION WATER USE EFFICIENCY IN SEMI-ARID REGIONS OF PAKISTAN. (October 2015) - UL-ALLAH, SAMI; KHAN, ASIF ALI; FRICKE, THOMAS; BUERKERT, ANDREAS; WACHENDORF, MICHAEL
SUMMARY In many parts of Pakistan, availability of green forage is critical to livestock farmers. Forage production is often conducted with two succeeding crops grown within one year and it is highly affected by uncertain availability of irrigation water and low levels of applied mineral fertilisers. The objectives of the present study were to (i) evaluate the effects of crop species, fertiliser type and irrigation level on yield, (ii) determine the corresponding water use efficiency and (iii) investigate relationships between chlorophyll content and crop yield as a basis for a simple sensor-based prediction of crop yield for on-farm use. To this end a two-year field experiment was conducted in Faisalabad, Pakistan, with a completely randomised design with four replications in a split plot arrangement. A combination of fertiliser treatment (control, farm yard manure and mineral fertiliser) and irrigation (recommended irrigation, half recommended irrigation) were assigned to main plot whereas subplots were assigned to cropping systems (common (CCS): Egyptian clover (Trifolium alexandrinum L.) followed by corn (Zea mays L.), drought-adapted (DACS): Oat (Avena sativa L.) followed by Sudangrass (Andropogon sorghum subsp. drummondii). Yield and irrigation water use efficiency of DACS was higher than CCS (14.8 and 26% respectively), the differences were bigger with reduced irrigation and fertilised crops used the available water better than the control. Positive linear relationships were found between chlorophyll concentration estimated by a chlorophyll meter and yield for all crops (r2 = 0.63–0.96), suggesting this technique as a fairly accurate approach to predict yields of crops in vegetative growth stage.